Phosphodiesterase PDE4D Is Decreased in Frontal Cortex of Aged Rats and Positively Correlated With Working Memory Performance and Inversely Correlated With PKA Phosphorylation of Tau - Leslie, Shannon N.; Datta, Dibyadeep; Christensen, Kyle R.; van Dyck, Christopher H.; Arnsten, Amy F. T.; Nairn, Angus C. (Frontiers in Aging Neuroscience, 2020)
Age is the largest risk factor for Alzheimer’s disease (AD) and contributes to cognitive impairment in otherwise healthy individuals. Thus, it is critical that we better understand the risk aging presents to vulnerable regions of the brain and carefully design therapeutics to address those effects. In this study we examined age-related changes in cAMP-regulatory protein, phosphodiesterase 4D (PDE4D). Inhibition of PDE4D is currently under investigation as a therapeutic target for AD based on memory-enhancing effects in rodent hippocampus. Therefore, it is important to understand the role of PDE4D in brain regions particularly vulnerable to disease such as the frontal association cortex (FC), where cAMP signaling can impair working memory via opening of potassium channels. We found that PDE4D protein level was decreased in the FC of both moderately and extremely aged rats, and that PDE4D level was correlated with performance on a FC-dependent working memory task. In extremely aged rats, PDE4D was also inversely correlated with levels of phosphorylated tau at serine 214 (S214), a site phosphorylated by protein kinase A. In vitro studies of the PDE4D inhibitor, GEBR-7b, further illustrated that inhibition of PDE4D activity enhanced phosphorylation of tau. pS214-tau phosphorylation is associated with early AD tau pathology, promotes tau dissociation from microtubules and primes subsequent tau hyperphosphorylation at other critical AD-related sites. Age-related loss of PDE4D may thus contribute to the specific vulnerability of the FC to degeneration in AD, and play a critical role in normal cAMP regulation, cautioning against the use of pan-PDE4D inhibitors as therapeutics.